Prevalence of Dental Fluorosis in the Primary Dentition - John J. Warren, DDS, MS; Steven M. Levy, DDS, MPH; Michael J. Kanellis, DDS, MS (Blackwell Synergy, 2001)
This paper presents data on the prevalence of primary tooth fluorosis among children residing in Iowa, and the relationships between fluorosis prevalence and selected measures of fluoride exposures.